Right to Place: A Political Theory of Animal Rights in Harmony with Environmental and Ecological Principles - Panagiotarakou, Eleni (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2014)
The focus of this paper is on the “right to place” as a political theory of wild animal rights. Out of the debate between terrestrial cosmopolitans inspired by Kant and Arendt and rooted cosmopolitan animal right theorists, the right to place emerges from the fold of rooted cosmopolitanism in tandem with environmental and ecological principles. Contrary to terrestrial cosmopolitans—who favour extending citizenship rights to wild animals and advocate at the same time large-scale humanitarian interventions and unrestricted geographical mobility—I argue that the well-being of wild animals is best served by the right to place theory on account of its sovereignty model. The right to place theory advocates human non-interference in wildlife communities, opposing even humanitarian interventions, which carry the risk of unintended consequences. The right to place theory, with its emphasis on territorial sovereignty, bases its opposition to unrestricted geographical mobility on two considerations: (a) the non-generalist nature of many species and (b) the potential for abuse via human encroachment. In a broader context, the advantage of the right to place theory lies in its implicit environmental demands: human population control and sustainable lifestyles.